Analisis Rasio Keuangan Untuk Memprediksi Kebangkrutan Dengan Model Altman Z-Score - Gabriella Handayani; Putu Gede Wisnu Permana Kawisana (Universitas Warmadewa, 2023)
This study discusses predicting bankruptcy with the Altman Z-score model in automotive and component sub-sector companies. Companies with the characteristics of financial distress are shown if they are not handled properly, they will cause the company to be vulnerable to bankruptcy. The research was conducted using the Z-score model which is able to provide predictions in 3 categories based on financial statements, namely: non-bankrupt, gray and bankrupt. The purpose of this study was to identify and perform a bankruptcy prediction analysis for automotive and components sub-sector companies on the Indonesia Stock Exchange in 2016–2020 that experienced financial distress using the Altman Z-score research model analysis. The samples used were 7 companies with the method of determining using purposive sampling. Based on the results of data analysis, it is known that in 2016 there are 4 companies predicted to be non-bankrupt, 1 company in the gray category, and 2 companies predicted to experience bankruptcy; 2017 with 5 companies predicted non-bankruptcy and 2 companies predicted bankruptcy; In 2018-2020 it is predicted that 3 companies will be in the non-bankrupt category, 2 companies will be in the gray category, and 2 companies will experience bankruptcy.